2014
DOI: 10.1371/journal.pone.0103540
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Sensitization with Ragweed Pollen Induces Local-Allergic-Rhinitis-Like Symptoms in Mice

Abstract: Recently, the concept of local allergic rhinitis (LAR) was established, namely rhinitis symptoms with local IgE production and negative serum antigen-specific IgE. However, the natural course of LAR development and the disease pathogenesis is poorly understood. This study investigated the pathophysiology of mice with allergic rhinitis that initially sensitized with ragweed pollen through the nasal route. Mice were nasally administrated ragweed pollen over consecutive days without prior systemic immunization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 37 publications
(60 reference statements)
1
45
0
Order By: Relevance
“…DEP disrupted the TJs between nasal epithelial cells and increased paracellular permeability of the epithelium. However, the current study used ragweed pollen, which has intrinsic adjuvant activity and does not require other adjuvants for nasal sensitization [27]. DEP exacerbated sneezing in mice with ragweed-pollen-specific AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEP disrupted the TJs between nasal epithelial cells and increased paracellular permeability of the epithelium. However, the current study used ragweed pollen, which has intrinsic adjuvant activity and does not require other adjuvants for nasal sensitization [27]. DEP exacerbated sneezing in mice with ragweed-pollen-specific AR.…”
Section: Discussionmentioning
confidence: 99%
“…The production of Th2 cytokines, IL-4, IL-5, and IL-13, from cLN cells by in vitro restimulation with ragweed antigen was comparable between ragweed-alone-challenged and ragweed-plus-DEP-challenged groups (Fig. Numbers of eosinophils in the nasal mucosa, which represent late-phase responses of AR and are largely dependent on Th2 cell activation [19,27], were similar between the groups (Fig. Numbers of eosinophils in the nasal mucosa, which represent late-phase responses of AR and are largely dependent on Th2 cell activation [19,27], were similar between the groups (Fig.…”
Section: Intranasal Co-administration Of Diesel Exhaust Particles Examentioning
confidence: 98%
“…WT and Fcer1a 2/2 mice, deficient for FcεRI and thus deficient for IgE-mediated allergic reactions, 9,37 were i.p. immunized with Ef-OVA 3 times (days 218, 211, and 24), then i.n.…”
Section: Ec-ova Elicits Ige-independent Rhinitismentioning
confidence: 99%
“…AR diagnosis is based on rhinitis symptoms: sneezing, nasal discharge, and nasal clotting, and the presence of systemic or local (nasal) allergen-specific IgE. [8][9][10] Patients with rhinitis without allergen-specific IgE are diagnosed as suffering from nonallergic rhinitis (NAR) and, in most cases, triggers of the symptoms are unclear. 11 Although NAR is not considered an allergy, some patients with NAR show nasal infiltration of inflammatory cells including neutrophils, eosinophils, and mast cells that suggests local activation of innate and/or adaptive immunity.…”
mentioning
confidence: 99%
“…Kato and colleagues investigated the pathophysiology of mice with allergic rhinitis that initially sensitized with ragweed pollen through the nasal route [Kato et al 2014]. The results demonstrated that nasal sensitization with an allergen induced systemic atopy, which can adversely affect the onset of other allergic diseases when the individuals encounter the same allergen.…”
Section: New Advances and Clinical Trials In 2014mentioning
confidence: 99%